Effect of Electro-Acupuncture on Lateralization of the Human Swallowing Motor Cortex Excitability by Navigation-Transcranial Magnetic Stimulation-Electromyography - Tang, Xiaorong; Xu, Mindong; Zhao, Jiayi; Shi, Jiahui; Zi, Yingyu; Wu, Jianlu; Xu, Jing; Yu, Yanling; Yao, LuLu; Ou, Jiayin; Li, Yitong; Yao, Shuqi; et al. (Frontiers in Behavioral Neuroscience, 2022)
Background The use of transcranial magnetic stimulation combined with electromyography for the functional evaluation of the cerebral cortex in both clinical and non-clinical populations is becoming increasingly common. Numerous studies have shown that electro-acupuncture (EA) can regulate cerebral cortical excitability. However, the effect of EA on the lateralization of the human swallowing motor cortex excitability is not yet fully understood. Objective The aim of this study was to assess whether lateralization is present in the swallowing motor cortex of healthy subjects, and to investigate the impact of EA at Lianquan (CV23) and Fengfu (GV16) on lateralization. Methods Forty subjects were randomized 1:1 into the EA group and the sham-EA group. The bilateral swallowing motor cortices was located by a neuroimaging navigation system. Then, the resting motor threshold (RMT) and motor evoked potential (MEP) of the mylohyoid of healthy subjects were recorded while applying combined transcranial magnetic stimulation and electromyography before and after EA or sham-EA. Results First, the RMT and MEP latency of the contralateral mylohyoid innervated by the right swallowing cortex (71.50 ± 1.67%, 8.30 ± 0.06 ms) were lower than those innervated by the left (79.38 ± 1.27%, 8.40 ± 0.06 ms). Second, EA at CV23 and GV16 reduced the bilateral RMT and enhanced the bilateral MEP latency and amplitude (P = 0.005, P < 0.001; P = 0.002, P = 0.001; P = 0.002, P = 0.009), while sham-EA did not (P > 0.05). Third, EA had an effect on the RMT and MEP latency in terms of lateralization changes, but this was not significant (P = 0.067, P = 0.156). Conclusion The right swallowing motor cortex of healthy subjects is more excitable than that of the left at resting state. Thus, we found that lateralization is present in the swallowing motor cortex of healthy people, which might indicate a hemispheric dominance of swallowing predominates in the right swallowing motor cortex. In addition, EA at CV23 and GV16 can instantly promote the excitability of the bilateral swallowing motor cortices. But there was no significant difference in EA stimulation in terms of lateralization.